Perfectly confident how to calibrate your decisions wisely - Moore, Don A. 1970- (Harper Business, 2020)
"Is confidence always a good thing? Don Moore, Professor of Management of Organizations at the Haas School of Business, argues that confidence is good, but overconfidence can hinder growth"--
Includes bibliographical references and index
Keywords: Communication in management; Confidence